Contributing Factors to Disease Outbreaks Associated with Untreated Groundwater. Issue 6 (3rd October 2013) - Wallender, Erika K.; Ailes, Elizabeth C.; Yoder, Jonathan S.; Roberts, Virginia A.; Brunkard, Joan M.
Abstract Disease outbreaks associated with drinking water drawn from untreated groundwater sources represent a substantial proportion (30.3%) of the 818 drinking water outbreaks reported to CDC's Waterborne Disease and Outbreak Surveillance System (WBDOSS) during 1971 to 2008. The objectives of this study were to identify underlying contributing factors, suggest improvements for data collection during outbreaks, and inform outbreak prevention efforts. Two researchers independently reviewed all qualifying outbreak reports (1971 to 2008), assigned contributing factors and abstracted additional information (e.g., cases, etiology, and water system attributes). The 248 outbreaks resulted in at least 23, 478 cases of illness, 390 hospitalizations, and 13 deaths. The majority of outbreaks had an unidentified etiology (n = 135, 54.4%). When identified, the primary etiologies were hepatitis A virus (n = 21, 8.5%), Shigella spp. (n = 20, 8.1%), and Giardia intestinalis (n = 14, 5.7%). Among the 172 (69.4%) outbreaks with contributing factor data available, the leading contamination sources included human sewage (n = 57, 33.1%), animal contamination (n = 16, 9.3%), and contamination entering via the distribution system (n = 12, 7.0%). Groundwater contamination was most often facilitated by improper design, maintenance or location of the water source or nearby waste water disposal system (i.e., septic tank; n = 116, 67.4%). Other contributing factors included rapid pathogen transport through hydrogeologic formations (e.g., karst limestone; n = 45, 26.2%) and preceding heavy rainfall or flooding (n = 36, 20.9%). This analysis underscores the importance of identifying untreated groundwater system vulnerabilities through frequent inspection and routine maintenance, as recommended by protective regulations such as Environmental Protection Agency's (EPA's) Groundwater Rule, and the need for special consideration of the local hydrogeology.